Effects of mindfulness-based stress reduction on perioperative outcomes in patients with advanced hepatocellular carcinoma undergoing transarterial chemoembolization - Yunyun Zhao; Juanjuan Li; Xiaobei Li; Mao Zhang; Jingxia Qin (PLoS ONE, 2026)
Objective To evaluate the effects of mindfulness-based stress reduction (MBSR) combined with standard perioperative care on perioperative outcomes in patients with advanced hepatocellular carcinoma (HCC) undergoing transarterial chemoembolization (TACE). Methods This retrospective study enrolled patients with advanced HCC who underwent TACE and received either standard perioperative care alone or standard care combined with an MBSR intervention. Post-embolization syndrome (PES) was assessed 72 hours after TACE. Postoperative pain was evaluated using the numerical rating scale (NRS), while anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS). Self-care efficacy was measured using the Strategies Used by People to Promote Health (SUPPH) scale. Univariate and multivariable logistic regression analyses were performed to explore factors associated with PES. Results Compared with standard care, the MBSR intervention was associated with significantly lower postoperative NRS pain scores at all assessed time points, reduced use and escalation of analgesic medications, and lower anxiety and depression scores (all P < 0.05). Patients in the mindfulness group also demonstrated significantly higher SUPPH scores, indicating better self-care efficacy ( P < 0.001). In addition, the incidence of PES and postoperative length of hospital stay were significantly lower in the mindfulness group. Logistic regression analysis showed that the mindfulness intervention was independently associated with a reduced risk of PES (OR = 0.55, 95% CI 0.31–0.96). Conclusion Mindfulness-based stress reduction combined with standard perioperative care was associated with improved pain control, psychological well-being, self-care efficacy, and reduced perioperative complications in patients with advanced HCC undergoing TACE. This intervention may serve as a feasible supportive approach in perioperative clinical practice.